Changes in microbial community succession and volatile compounds during the natural fermentation of bangcai - Xie, Lili; Wang, Xueli; Wang, Xiujun; Liu, Xueting (Frontiers in Microbiology, 2025)
IntroductionFermented bangcai (Brassica juncea var. crassicaulis) is a traditional Chinese food with unique flavor. However, the formation mechanism of flavor compounds related to the fermentation process of bangcai has not been thoroughly studied.MethodsGas chromatography-ion mobility spectrometry technology combined with metagenomics was used to analyze the characteristic volatile flavor compounds and microbial community structure of bangcai before and after fermentation in this study.ResultsA total of 91 types of volatile organic compounds were detected in this study. The pungent odor brought by allyl isothiocyanate, 1-butene isothiocyanate, and other substances in the raw materials was removed through fermentation. This process led to the formation of flavor substances such as propyl acetate, ethyl acetate, and 2-methyl-3-furanthiol, which imparted bangcai with flavors of flower and fruit, roast meat, and fried coffee. In addition, our study found that after air drying, bangcai mainly contained γ-butyrolactone, nonanal and other flavor compounds, giving the bangcai products a richer floral and fruity flavor profile. Citrobacter, Lactobacillus, and Leuconostoc were the dominant bacteria in the fermentation process of bangcai. They were significantly related to the formation of differential flavor compounds such as γ-butyrolactone, ethyl 2-methylpropanoat, and benzaldehyde-D.DiscussionThese results provide a theoretical basis for improving the flavor quality of fermented vegetable products.